Interpretation of customary international law : of methods and limits - Merkouris, Panos (Brill research perspectives in international legal theory and practice., 2024)
Whereas the identification of rules of customary international law, through general practice and opinio juris, has been dealt extensively in literature and practice, their interpretation has remained surprisingly unexplored. It is this gap that this short monograph aims to address.